Symposium 7: Online Learning Community Research - Some Influences of Theory on Methods - Harris, Rachel; Muirhead, Alison (Proceedings of the International Conference on Networked Learning, 2004)
This paper presents different perspectives on research in the field of online learning communities. To highlight the range of theoretical backgrounds and frameworks that are influencing research in this area, a brief outline is given of investigations into social networks and bonding; affordances of online communities; identity and presence; and community ‘building’. This serves to emphasise the diversity of approaches being applied, and the value of drawing from the theory of a wide range of disciplines. Combined with the difficulties of even attempting to compare methodologies or results across studies in this area, the need for some form of common ground is very clear.